Application of Realistic Mathematic Education And Classroom Assassement Approach Toward Cuboid Materials On The Effectiveness of Learning Outcomes For 5th Grade Students In MI Miftahul Ulum I And II - Dyah Qurrota A'yuni (Hipotenusa : Journal of Mathematical Society, 2020)
AbstractThis thesis discusses the effectiveness of applying the Realistic Mathematic Education (RME) Approach and Classroom Assessment to the learning outcomes of Class V students on cuboids material in MI Miftahul Ulum I and II in the academic year 2019/2020. This study is motivated by the lack of students' understanding of mathematics which is basically closely related to the real things that are around. From the research that has been carried out regarding the effectiveness of the application of the Realistic Mathematic Education (RME) and Classroom Assessment approach to Mathematics learning outcomes of the subject matter of cuboids material of students in class V MI Miftahul Ulum I and II Honggosoco in the academic year 2019/2020, the research was conducted using the method experiment and it can be concluded that, based on data analysis and discussion stated earlier in chapter IV and also based on the average test of one party, then the analysis of learning outcomes based on the average difference test of one party is obtained = 3,832 dan = 2,011. Because tcount ttable, then it is significant and the proposed hypothesis can be accepted. The average learning outcomes of students given teaching by applying the development of a Realistic Mathematic Education (RME) approach and Classroom Assessment is better at 66.64 compared to the average learning outcomes of students given teaching using conventional learning that is 54.92.